2017
DOI: 10.1523/jneurosci.1453-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

After Nerve Injury, Lineage Tracing Shows That Myelin and Remak Schwann Cells Elongate Extensively and Branch to Form Repair Schwann Cells, Which Shorten Radically on Remyelination

Abstract: There is consensus that, distal to peripheral nerve injury, myelin and Remak cells reorganize to form cellular columns, Bungner's bands, which are indispensable for regeneration. However, knowledge of the structure of these regeneration tracks has not advanced for decades and the structure of the cells that form them, denervated or repair Schwann cells, remains obscure. Furthermore, the origin of these cells from myelin and Remak cells and their ability to give rise to myelin cells after regeneration has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
208
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(218 citation statements)
references
References 41 publications
9
208
1
Order By: Relevance
“…As detailed in the following section, Schwann cells provide a further example of adaptive cellular reprogramming. In this case also, cells with a repair‐supportive phenotype, which are normally absent, are generated directly from resident differentiated cells of the injured tissue (Gomez‐Sanchez et al, ) and function to restore tissue homeostasis.…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
See 2 more Smart Citations
“…As detailed in the following section, Schwann cells provide a further example of adaptive cellular reprogramming. In this case also, cells with a repair‐supportive phenotype, which are normally absent, are generated directly from resident differentiated cells of the injured tissue (Gomez‐Sanchez et al, ) and function to restore tissue homeostasis.…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
“…(c) Structural reorganization, generating extremely elongated, cells, which are about threefold longer than myelin and Remak cells. Lineage tracing has shown that these cells are generated directly from myelin and Remak cells, and that they can convert directly to myelin cells following regeneration (Gomez‐Sanchez et al, ). These cells often carry long, parallel processes, which together with their length, allows repair cells to partly overlap and promotes the formation of the compact cellular columns (Bungner bands—Figures and ), which are obligatory regeneration tracks for regenerating axons (Gomez‐Sanchez et al, ).…”
Section: Adaptive Cellular Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…Repair Schwann cells activate autophagy and phagocytosis mechanisms to remove myelin debris, which inhibit axon regrowth and branching (Brosius Lutz et al 2017; Gomez-Sanchez et al 2015; Mukhopadhyay et al 1994; Shen et al 1998), and promote recruitment of macrophages that further facilitate myelin removal and regeneration (Cattin et al 2015; Fischer et al 2008; Niemi et al 2013). Elongated Schwann cells distal to the injury site form Bands of Bungner, which serve as tracks for axonal regeneration (Arthur-Farraj et al 2012; Gomez-Sanchez et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The regeneration of axons as well as motor and sensory target innervation after injury is dependent on the capacity of Schwann cells to switch into and maintain a repair phenotype (Büngner cell) . These repair Schwann cells support axonal growth and path‐finding.…”
Section: Discussionmentioning
confidence: 99%